2012
DOI: 10.1371/journal.pone.0037941
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Melanoma Metastasis and Immunosuppression with a New Mode of Melanoma Inhibitory Activity (MIA) Protein Inhibition

Abstract: Melanoma is the most aggressive form of skin cancer, with fast progression and early dissemination mediated by the melanoma inhibitory activity (MIA) protein. Here, we discovered that dimerization of MIA is required for functional activity through mutagenesis of MIA which showed the correlation between dimerization and functional activity. We subsequently identified the dodecapeptide AR71, which prevents MIA dimerization and thereby acts as a MIA inhibitor. Two-dimensional nuclear magnetic resonance (NMR) spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 25 publications
0
44
0
Order By: Relevance
“…MIA is a protein secreted by chondrocytes and as well as by melanoma cells. Probably the increased level of MIA in melanoma patients with poor prognosis is a potential indicator of pro-inflammatory status switch to a more antiinflammatory and immunosuppressive status of the disease, but further studies are needed to investigate the actual connection of MIA with inflammation 82 . Acute phase reactant proteins (APRPs) are usually produced by cytokine-stimulated hepatocytes (e.g.…”
Section: Circulatory Inflammatory Markersmentioning
confidence: 99%
“…MIA is a protein secreted by chondrocytes and as well as by melanoma cells. Probably the increased level of MIA in melanoma patients with poor prognosis is a potential indicator of pro-inflammatory status switch to a more antiinflammatory and immunosuppressive status of the disease, but further studies are needed to investigate the actual connection of MIA with inflammation 82 . Acute phase reactant proteins (APRPs) are usually produced by cytokine-stimulated hepatocytes (e.g.…”
Section: Circulatory Inflammatory Markersmentioning
confidence: 99%
“…In contrast, PER3 4/4 still did not show decreased brain responses to the task, but rather recruited supplemental brain areas located in right inferior frontal, middle temporal, parahippocampal gyri, as well as in bilateral thalamic areas. Similarly, morning types, more vulnerable to the accumulation of time spent awake throughout a normal waking day (Kerkhof, 1991; Mongrain et al, 2006a,b) show decreased BOLD responses in brain areas involved in conflict resolution over a normal waking day while performing the Stroop paradigm (Schmidt et al, 2012). In contrast, evening chronotypes, less affected by accumulated homeostatic sleep pressure during the evening exhibited the reversed profile or presented stable BOLD responses from morning to evening hours in task-related brain regions (Schmidt et al, 2012).…”
Section: Cerebral Correlates Underlying Circadian and Homeostatic Regmentioning
confidence: 99%
“…The synchrony effect applies to different cognitive domains, including short-term memory tasks such as word span measures (Yoon, 1997), performance on different long-term memory tasks (May and Hasher, 1998; Intons-Peterson et al, 1999; Winocur and Hasher, 2002), and executive functions, especially cognitive inhibition abilities (Intons-Peterson et al, 1998; May and Hasher, 1998; May, 1999; West et al, 2002). We have recently observed that adapting testing time according to the specific individual’s sleep-wake schedule can attenuate synchrony effects in PVT and Stroop tasks (Schmidt et al, 2012), suggesting that part of the reported synchrony effects in aging may be accounted for by a series of confounders (e.g., differences in socio-professional timing constraints, the amount of accumulated sleep need or circadian phase position, all modulating arousal level at testing) rather than being inherent to the chronotypical profile of an individual. In the same vein, time of season may also affect cognitive functions, especially in clinical populations, such as bipolar I disorder (Rajajarvi et al, 2010).…”
Section: Age-related Modulation In Circadian and Homeostatic Regulatimentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Bosserhoff et al [195], demonstrated that MIA-stimulated melanoma metastasis by promoting cellular detachment from the extracellular matrix in vivo [196] via reduced integrin activity and MAPK pathway [197]. MIA has become a potential target for new strategies in antitumor research because MIA inhibition reduced melanoma dissemination [198].…”
Section: Miamentioning
confidence: 99%